Fast and Optimized Calculation of the Cable Pretension Forces in Arch Bridges With Suspended Deck - Modano, Mariano; Majumder, Arnas; Santos, Filipe; Luciano, Raimondo; Fraternali, Fernando (Frontiers in Built Environment, 2020)
This paper deals with an effective and fast approach to the optimization of the pretension forces in arched bridges with suspended deck, which makes use of the influence matrix method. The given cable-tensioning procedure leads to a linear system of equations with a reduced number of unknowns and can be effectively implemented within active control procedures that handle time-varying loading conditions. It achieves of a target bending moment distribution over the structure, which significantly mitigates the state of stress of the deck. Numerical results dealing with a Nielsen arch bridge illustrate the versatility of the proposed approach when dealing with different loading conditions